Abnormal alpha modulation in response to human eye gaze predicts inattention severity in children with ADHD - Guo, Jialiang (Dev Cogn Neurosci, 2019)
Attention-deficit/hyperactivity disorder (ADHD) is characterized by problems in directing and sustaining attention. Recent behavioral studies indicated that children with ADHD are more likely to fail to show the orienting effect in response to human eye gaze. The present study aimed to identify the neurophysiological bases of attention deficits directed by social human eye gaze in children with ADHD, focusing on the relationship between alpha modulations and ADHD symptoms. The electroencephalography data were recorded from 8–13-year-old children (typically developing (TD): n = 24; ADHD: n = 21) while they performed a cued visuospatial covert attention task. The cues were designed as human eyes that might gaze to the left or right visual field. The results revealed that TD children showed a significant alpha lateralization in response to the gaze of human eyes, whereas children with ADHD showed an inverse pattern of alpha modulation in the left parieto-occipital area. Importantly, the abnormal alpha modulation in the left hemisphere predicted inattentive symptom severity and behavioral accuracy in children with ADHD. These results suggest that the dysfunction of alpha modulation in the left hemisphere in response to social cues might be a potential neurophysiologic marker of attention deficit in children with ADHD.